Saccharification of macroalgal polysaccharides through prioritized cellulase producing bacteria. Issue 3 (March 2019) - Hebbale, Deepthi; Bhargavi, R.; Ramachandra, T.V.
Abstract: Marine macroalgal cell wall is predominantly comprised of cellulose (polysaccharide) with the complex chain of glycosidic linkages. Bioethanol production from macroalgae entails breaking this complex chain into simple glucose molecule, which has been the major challenge faced by the industries. Cellulases have been preferred for hydrolysis of cellulose due to the absence of inhibitors affecting the subsequent fermentation process. Cellulose degrading bacteria were isolated from wide-ranging sources from marine habitats to herbivore residues and gastrointestinal region. The investigation reveals that Vibrio parahaemolyticus bacteria has higher hydrolytic capacity with salt tolerance up to 14% and 3.5% salinity is optimum for growth. Higher hydrolytic activity of 2.45 was recorded on carboxymethyl cellulose medium at 48 h and hydrolytic activity of 2.46 on Ulva intestinalis hydrolysate, 3.06 on Ulva lactuca hydrolysate at 72 h of incubation. Total activity of enzyme of 2.11 U/ml and specific activity of 6.05 U/mg were recorded at 24 h. Enzyme hydrolysis of macroalgal biomass; U. intestinalis and U. lactuca produced 135.9 mg/g and 107.6 mg/g of reducing sugar respectively. The study reveals that the enzyme extracted from salt tolerant Vibrio parahaemolyticus bacteria is suitable for optimal saccharification of seaweed polysaccharides towards biofuel production.